Genetic methods in honey bee breeding - M. D. Kaskinova; A. M. Salikhova; L. R. Gaifullina; E. S. Saltykova (Вавиловский журнал генетики и селекции, 2023)
The honey bee Apis mellifera is a rather difficult object for selection due to the peculiarities of its biology. Breeding activities in beekeeping are aimed at obtaining bee colonies with high rates of economically useful traits, such as productivity, resistance to low temperatures and diseases, hygienic behavior, oviposition of the queen, etc. With two apiaries specializing in the breeding of A. m. mellifera and A. m. carnica as examples, the application of genetic methods in the selection of honey bees is considered. The first stage of the work was subspecies identification based on the analysis of the polymorphism of the intergenic mtDNA locus tRNAleu-COII (or COI-COII) and microsatellite nuclear DNA loci Ap243, 4a110, A24, A8, A43, A113, A88, Ap049, A28. This analysis confirmed that the studied colonies correspond to the declared subspecies. In the apiary with A. m. mellifera, hybrid colonies have been identified. A method based on the analysis of polymorphisms of the tRNAleu-COII locus and microsatellite nuclear DNA loci has been developed to identify the dark forest bee A. m. mellifera and does not allow one to differentiate subspecies from C (A. m. carnica and A. m. ligustica) and O (A. m. caucasica) evolutionary lineages from each other. The second stage was the assessment of the allelic diversity of the csd gene. In the apiary containing colonies of A. m. mellifera (N = 15), 20 csd alleles were identified. In the apiary containing colonies of A. m. carnica (N = 44), 41 alleles were identified. Six alleles are shared by both apiaries. DNA diagnostics of bee diseases showed that the studied colonies are healthy. Based on the data obtained, a scheme was developed for obtaining primary material for honey bee breeding, which can subsequently be subjected to selection according to economically useful traits. In addition, the annual assessment of the allelic diversity of the csd gene will shed light on the frequency of formation of new allelic variants and other issues related to the evolution of this gene.